A Class of Meromorphic Multivalent Functions with Positive Coefficients Defined by Struve Function - Hamaad, Suha J.; Juma, Abdul Rahman S.; Ebrahim, Hassan H. (Iraqi Journal of Science, 2025)
The main goal of this work is to obtain new geometric properties for meromorphic multivalent functions in the punctured disk 〖 (UD)〗^*=UD{0=z:z∈C and 0< |z|<1, so we presented a new class〖 J〗_(c,p)^(ζ,a) (β,δ,б) by using Hadamard product. In this paper we obtained many important properties such as coefficient estimates, radius of convexity, distortion theorem, convex combination and closure theorem. In addition, we derived the integral transforms and Hadamard product for functions belonging to the class 〖 J〗_(c,p)^(ζ,a) (β,δ,б).